Tyrosinase Inhibitors from the Aerial Parts of Wulfenia carinthiaca jacq. - Mutschlechner, Benjamin (John Wiley and Sons Inc., 2018)

(untitled) (Chem Biodivers)
Activity guided isolation of a MeOH extract of the aerial plant parts of Wulfenia carinthiaca jacq. (Plantaginaceae), using a mushroom tyrosinase assay, resulted in the isolation of five phenylethanoid glucosides and four iridoid glycosides. Two of them, 2′‐O‐acetylisoplantamajoside and 2′,6″‐O‐diacetylisoplantamajoside, represent new natural products. Evaluation of the inhibitory activity of all isolated compounds revealed that the observed activity is not related to the isolated phenylethanoid glycosides but mainly due to the presence of the iridoid glycoside globularin (IC (50) 41.94 μm;CI (95%) ± 16.61/11.89 μm). Interestingly, structurally close related compounds (globularicisin, baldaccioside, and isoscrophularioside) showed no or only a weak tyrosinase inhibitory activity.